Delivery of Psychological Skills Training to Youngsters. Issue 1 (2nd January 2016) - Foster, David; Maynard, Ian; Butt, Joanne; Hays, Kate
Abstract : The aim of the present study was to explore sport psychologists' experiences of working with children and adolescents to understand how they have adapted both content and delivery of psychological skills training when consulting with young athletes. Interviews with 12 experienced sport psychology consultants from the United Kingdom were inductively content analyzed. Four main higher order themes relating to content and delivery emerged: consultancy skills, relating to youngsters, delivery medium, and maintaining engagement. The findings imply that psychologists experience challenges unique to youth populations but also have developed content and delivery strategies to overcome these.